Cytotoxic and genotoxic potential of geraniol in peripheral blood mononuclear cells and human hepatoma cell line (HepG2) - Queiroz, T. B. [UNESP]; Santos, G. F. [UNESP]; Ventura, S. C. [UNESP]; Hiruma-Lima, C. A. [UNESP]; Gaivao, I. O. M.; Maistro, E. L. [UNESP] (Funpec-editora, 2017)
Geraniol is an acyclic monoterpene alcohol present in the essential oil of many aromatic plants and is one of the most frequently used molecules by the flavor and fragrance industries. The literature also reports its therapeutic potential, highlighting itself especially as a likely molecule for the development of drugs against cancer. In view of these considerations, this study was designed to evaluate the cytotoxic and genotoxic potential of geraniol, in an in vitro protocol, using two types of human cells: one without the ability to metabolize (peripheral blood mononuclear cells - PBMC), and the other with this capability (human hepatoma cell line - HepG2) through the comet assay and the micronucleus test. Four concentrations (10, 25, 50, and 100 mu g/mL) were selected for the genotoxic assessment for PBMC and three (1.25, 2.5, and 5 mu g/mL) for HepG2 cells based on cytotoxicity tests (MTT assay). Results showed that geraniol did not present genotoxic or clastogenic/aneugenic effects on both cell types under the conditions studied. However, caution is advised in the use of this substance by humans, since a significant reduction in viability of HepG2 and a marked decrease in cell viability on normal PBMC were verified.
Keywords: Monoterpene; Geraniol; Comet assay; Micronucleus test; MTT assay